Study of Cryptocurrency Transaction through Fiqih Rules Approach (Qawa`id Fiqhiyah) - lutfi bangun lestari (UIN Sulthan Thaha Saifuddin Jambi, 2023)
Cryptocurrency is a digital currency as part of the results of technological innovation and development. Its flexible existence makes people interested in making transactions with this cryptocurrency. The function of this currency is not much different from fiat currency in general, but crypto currency does not have a physical form because transactions use the internet network. So in this study, after conducting an analysis, it was found that the phenomenon of cryptocurrency transactions is included in the fiqh rules regarding harm and customs, according to the fiqh rules regarding the damage that a person is prohibited from committing acts that could endanger himself and also other people where the high fluctuating prices lead to speculation, which can cause harm, namely the risk of economic bubbles. Basically, the existence of cryptocurrency as a virtual currency is permissible because it has been recognized by various communities, but it must see legality and recognition by the government as a right and obligation of the government. Included in the issuance of the currency. Based on the analysis of fiqh rules about customs. It can be explained that cryptocurrency transactions are included in 'urf fasid because the transactions do not meet the requirements of 'urf authentic, even though their existence has begun to be recognized by the public so that it can be concluded that cryptocurrency transactions during observations through the fiqh rule approach have not found aspects that allow cryptocurrency transactions to be included in transactions that are prohibited by the Shari'a because they contain speculation that gives rise to gharar and maysir. Future prospects cannot be known because there are no underlying assets, and there is no financial authority to oversee them.